An integrated multi-omics analysis identifies prognostic molecular subtypes of non-muscle-invasive bladder cancer - Sia Viborg Lindskrog (Nature Portfolio, 2021)
Multiple molecular profiling methods are required to study urothelial non-muscle-invasive bladder cancer (NMIBC) due to its heterogeneity. Here the authors integrate multi-omics data of 834 NMIBC patients, identifying a molecular subgroup associated with multiple alterations and worse outcomes.